A restructuring of the Diocesan Superintendent's Office of Tandag Surigao Del Sur and the development of the Diocesan Superintendent's administrative manual - Falcon, Florio R., DCMS (Animo Repository, 1994)
This study assesses and, in turn, restructures the Diocesan Superintendent's Office (DSO) of Tandag, Surigao del Sur. To supplement the restructured DSO, an administrative manual for the Superintendent's Office was formulated. The researcher used an adapted survey questionnaire developed by Franco (1991). The questionnaire was given to the school administrators, faculty members, priest directors and parish priests, the staff, and other personnel of the 13 Diocesan schools. The data gathered in the survey were treated statistically by frequencies, weighted mean, and mean averages. In restructuring the DSO, the Project Planning and Management Cycle of Dennis Rondennelli was adopted in the second phase of the study. In formulating the DSO administrative manual, the R & D Model of Borg was used as the development model. The three models used in this study were complemented by the formal and informal interviews with (1) the administrators of the Diocese of Tandag and (2) other administrators and faculty outside the said Diocese. They were interviewed during an annual convention, and a general assembly of the diocesan superintendents and regional directors of Bacolod City. The formal committee required by the model of Rondenneli and that of Borg was modified by a non-formal committee composed of the Bishop and school administrators who were consulted by the researcher in the course of his research. The outcome of the assessment of the DSO identified the need for restructuring the office due to its poor performance. This was indicated by the respondents who were unanimous in their high expectation of the office to deliver needed services. Such services included (1) supportive assistance to the current administration and (2) supervision of the diocesan schools. It was identified that the office could not deliver such services due to budgetary constraints, poor organization, and recruitment/hiring of people. The research restructured the DSO and formulated its administrative manual. A 3-year action plan was proposed in order to finalize the manual and institutionalize the restructured DSO.